2011
DOI: 10.1093/cid/cir377
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Trends and Risk Factors for Non-O157 Shiga Toxin-Producing Escherichia coli Found Through Shiga Toxin Testing, Connecticut, 2000-2009

Abstract: Both O157 and non-O157 STEC infection incidence decreased from 2000 through 2009. Although infection due to O157 is the most common and clinically severe STEC infection, it accounts for a minority of all clinically significant STEC infections. STEC appear to be a diverse group of organisms that have some differences as well as many epidemiologic and exposure features in common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 14 publications
6
41
2
1
Order By: Relevance
“…Although previously the majority of reported cases were attributed to E. coli O157:H7 and many recent studies indicate higher incidence rates of HUS associated with E. coli O157:H7 (3,4), non-O157 STEC serotypes are emerging as important etiological agents of both sporadic cases and community outbreaks of diarrhea (3)(4)(5)(6)(7)(8). Most notably, in May and June 2011, a large outbreak of E. coli O104:H4-associated diarrheal illness in Germany led to HUS in over 800 patients, many of whom were adults, and ultimately resulted in 54 deaths (5,9).…”
mentioning
confidence: 97%
“…Although previously the majority of reported cases were attributed to E. coli O157:H7 and many recent studies indicate higher incidence rates of HUS associated with E. coli O157:H7 (3,4), non-O157 STEC serotypes are emerging as important etiological agents of both sporadic cases and community outbreaks of diarrhea (3)(4)(5)(6)(7)(8). Most notably, in May and June 2011, a large outbreak of E. coli O104:H4-associated diarrheal illness in Germany led to HUS in over 800 patients, many of whom were adults, and ultimately resulted in 54 deaths (5,9).…”
mentioning
confidence: 97%
“…Findings from several of these studies are particularly worth mentioning. Of 229 Connecticut patients with infections caused by non-O157:H7 STEC/ VTEC who were studied over a decade-long interval (48), HUS developed in only one, while HUS developed in 45 of the 434 patients in this series who were infected with E. coli O157. In a United States-wide study of 83 patients with HUS (12), 70 patients had stool cultures in which bacteria grew.…”
Section: Distinction Between Stec/vtec Belonging To Serotype O157:h7 mentioning
confidence: 88%
“…As noted above, E. coli O157:H7 is the overwhelming cause of postdiarrheal HUS (8,12,16,21,(43)(44)(45)(46)(47)(48)(49). If the stool of a patient with HUS does not contain E. coli O157:H7, the most likely explanation is that the specimen was first cultured for this organism at a point in illness when the pathogen had been eliminated (44).…”
Section: Distinction Between Stec/vtec Belonging To Serotype O157:h7 mentioning
confidence: 98%
See 1 more Smart Citation
“…To date, over 100 different serotypes of STEC have been identified, all causing bacterial gastroenteritis in humans and some known to induce haemorrhagic colitis and haemolytic uremic syndrome (HUS) (10). Numerous studies have reported that STEC-related illness is not always associated with fever and haemorrhagic colitis and is not restricted to a particular season (16). Recently, a large outbreak of HUS caused by this bacteria (O104:H4) occurred in Europe, affecting more than 4000 patients with diarrhoeal disease and resulting in the death of about 54 patients (4,11).…”
Section: Introductionmentioning
confidence: 99%